Предмет: Алгебра,
автор: Аноним
Решите уравнение (х+1)(х-6)/х^2-36=0
Ответы
Автор ответа:
0
(x+1)(x-6)/(x-6)(x+6)=0;
(x+1)/(x+6)=0;
Домножаем на (х+6). Имеем:
(Х+1)(х+6)=0;
х^2+7х+6=0.
В результате решения квадратного уравнения получаем: х1=-6; х2=-1.
(x+1)/(x+6)=0;
Домножаем на (х+6). Имеем:
(Х+1)(х+6)=0;
х^2+7х+6=0.
В результате решения квадратного уравнения получаем: х1=-6; х2=-1.
Похожие вопросы
Предмет: Биология,
автор: sashakiriluk04
Предмет: Математика,
автор: sofy160209
Предмет: Другие предметы,
автор: Аноним
Предмет: Математика,
автор: VegaMega
Предмет: Геометрия,
автор: alina9d